Effectiveness of ischemic compression pressure versus spray and stretch technique in the management of active myofascial trigger points of trapezius muscle. - Khan, Urooj; Akhter, Saeed; Khan, Muhammad; Mirza Baig, Aftab Ahmed (International Journal of Endorsing Health Science Research, 2021)
Background: Now, a days myofascial trigger points are tremendously occurring and become a stressful part of nearly any person at any time in a lifetime. This study compares the effects of ischemic compression pressure with spray and stretch technique to treat active myofascial trigger points of the trapezius muscle in patients with neck pain. Methodology: A comparative interventional study was conducted at Dow University of Health Sciences from December 2016 and May 2017. Seventy patients (35 in each group) with active myofascial trigger points of trapezius were randomly assigned to group A (ischemic compression pressure) and group B (vapocoolant spray and stretch technique). Baseline and last session assessment of pain intensity, pain pressure tolerance, cervical range of motion and functional disability were measured through numerical pain-rating scale, algometer, goniometer and neck disability index, respectively. Results: Both groups showed significant improvement in all dependent variables of study which were neck pain, cervical range of motion and pain pressure tolerance (p-value<0.05). Group A showed greater improvement in pain intensity (p-value 0.015), pressure pain threshold (p-value 0.000) and cervical range of motion flexion, left side flexion and right-side flexion (p-value 0.002, 0.000 & 0.004) than group B. Conclusion: Both ischemic compression pressure & spray and stretch technique deactivated trigger points of upper fibers trapezius muscle in patients with neck pain, but the ischemic compression pressure was superior to the spray and stretch technique.